Metal−Organic Frameworks: Why Make Them Small?. Issue 1 (13th January 2022) - Wang, Jiemin; Imaz, Inhar; Maspoch, Daniel
Abstract : Metal–Organic Frameworks Metal–organic frameworks (MOFs) can be miniaturized down to the sub‐microscale and even nanoscale exhibiting size‐dependent properties, similarly to other nanoparticles. In article number 2100126 by Jiemin Wang, Inhar Imaz, and Daniel Maspoch, the basic concepts and recent progress concerning the core question of "MOFs, why make them small?" are briefly introduced from three perspectives: size, shape and processability.